Post‐Traumatic Shoulder Movement Disorders: A Challenging Differential Diagnosis Between Organic and Functional. Issue 2 (19th May 2014) - Pandey, Sanjay; Nahab, Fatta; Aldred, Jason; Nutt, John; Hallett, Mark
Abstract Peripheral trauma may be a trigger for the development of various movement disorders, though the pathophysiology remains controversial and some of these patients have a functional (psychogenic) disorder. We report on 3 cases of shoulder movement disorders subsequent to trauma to the shoulder region. Physiology was done in all the patients to extend the physical examination. Two patients had a history of recurrent shoulder dislocation and were diagnosed with Ehlers‐Danlos syndrome. One patient had shoulder injury after repeated falls while performing as a cheerleader. In 2 patients, there were some clinical features suggesting a functional etiology, but physiological studies in all 3 failed to produce objective evidence of a functional nature. Shoulder movement after trauma is uncommon. Diagnosis in such cases is challenging, considering the complex pathophysiology. The movements can be associated with prolonged pain and handicap, and once established, they appear resistant to treatment.